A new optotype and chart for precision visometry - A-G. D. Aliev; A. A-G. Aliev; M. M. Nurudinov (Российский офтальмологический журнал, 2019)
Purpose. To develop a new optotype and a chart for precision visometric tests and assess their accuracy.Materials and methods. 56 patients aged 16 to 57 years with the maximum visual acuity (VA) of 1.0 or more were examined for VA using three types of optotypes: standard letter optotype based on the Sivtsev — Golovin table, Landolt rings, and a new optotype developed by the authors.Results. On the basis of the psychometric analysis, the corresponding curves were drawn. When using the new optotype, the share of correct answers for VA = 1.0 was 75 %, for VA = 1.5 — 25 %, and for VA = 2.0 — 10 %. In contrast, Landolt rings and Sivtsev — Golovin optotypes gave the following results, respectively: VA = 1.0 — 50 %, 1.5 — 20 %, 2.0 — 10 % and VA = 1.0 — 45 %, VA = 1.5 — 15 %, VA = 2.0 — 5 %.Conclusion. The proposed optotype and the table for visometric tests, based on the principle of logarithmic progression of optotype sizes, significantly increase the accuracy of VA assessment. An extended range of optotype sizes increases the sensitivity of the visometry.